PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA BENGKEL SEPEDA MOTOR YAMAHA SIP PANJI DI SITUBONDO - Halisatil Imani; Dassucik Dassucik; Ahmad Hafas Rasyidi (LPPM Politeknik Pratama, 2025)
In the business world, especially in the service sector such as motorcycle repair shops, fierce competition makes customer satisfaction a key factor in maintaining loyalty and attracting new customers. The data collection technique used in this study was the distribution of questionnaires. The data analysis method employed multiple linear regression. The research results are as follows: Based on the table, it can be seen that the significance level of 277.864 > 3.093. Therefore, it can be concluded that the F-test > F-table value indicates a significant influence between price and service quality on customer satisfaction. To test the significance of the influence of price and service quality on customer satisfaction, a partial test was conducted when testing the influence of the price variable, which showed that the calculated t-value for (X1) was 3.361, while the t-table value at a 95% confidence level was 2.000. Since the calculated t-value is less than the t-table value, H0 is rejected and H1 is accepted, meaning that there is a significant influence between price and customer satisfaction. The service quality variable showed that the calculated t-value for (X2) was 3.291, while the t-table value at a 95% confidence level was 2.000. Since the calculated t-value < t-table, H0 is rejected and Ha is accepted, which means that there is a significant influence between service quality and customer satisfaction.